The perceived value and profile of Protected Areas Visitors: a case study of the Guayas Province, Ecuador - Carvache-Franco, Mauricio; Carvache-Franco, Orly; Solis-Radilla, María Magdalena; Carvache-Franco, Wilmer (Geographica Pannonica, 2019)
In the literature on tourism and travel, there is a large number of studies on the perceived value, however, natural protected areas and its relationship with the profile of the tourist has been little investigated. Hence, the importance of posing the main objective, to evaluate the relationship between the perceived value with the satisfaction and loyalty of the visitors of Morro Mangroves Wildlife Refuge, Santay Island National Recreation Area and Samanes National Recreation Area, three vulnerable protected areas located in the province of Guayas in Ecuador. The study was conducted in situ with 382 surveys, finding that the perceived values ​​that are related to satisfaction and loyalty were functional value and emotional value.
Keywords: tourism; perceived value; socio-demographic profile; protected natural areas